Montelukast promotes mitochondrial biogenesis via CREB/PGC-1α in human bronchial epithelial cells - Huan Wang; Yali Cheng; Ying Liu; Jiang Shi; Zhe Cheng (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Bronchial epithelial mitochondrial dysfunction including impaired mitochondrial biogenesis has been linked with the initiation and development of bronchial asthma. Montelukast, a robust antagonist of cysteinyl leukotriene receptors, has been widely applied for the therapies of bronchial asthma. However, the effects of montelukast in airway epithelial mitochondrial dysfunction are less reported. In the present study, we report that montelukast treatment in human bronchial epithelial cells of Beas-2b increased the expressions of PGC-1α, NRF-1 and TFAM. As expected, montelukast promoted mitochondrial biogenesis in Beas-2b cells through increasing mitochondrial mass, mtDNA/nDNA and the expression of cytochrome B. Importantly, we found that montelukast caused a functional gain in mitochondria of Beas-2b cells. Mechanistically, we found that montelukast treatment increased intracellular cAMP levels and activation of CREB. Blockage of CREB with H89 abolished montelukast-induced expression of PGC-1α. These findings report a novel pharmacological function of montelukast in stimulating mitochondrial biogenesis in Beas-2b cells, mediating by the CREB/PGC-1α pathway.